2004
DOI: 10.1016/j.annrmp.2004.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Évolution des prothèses des sprinters amputés de membre inférieur

Abstract: For about 15 years, technical advances in prosthetic treatment have been the main factor in the increased performance of athletes with lower-limb amputation. For trans-tibial amputation, the prosthesis for sprinting is composed of a gel liner and a socket joined by a locking or virtual vacuum liner. Because of these dynamic properties, the carbon prosthetic foot equipped with tacks ensures outstanding performance. For trans-femoral amputation, a hydraulic swing and a stance control unit are added to the same p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…With regard to unilateral lower limb amputees, two classes are acknowledged by World Para-Athletics and by the International Paralympic Committee (IPC) [33]: Class T63, where competitors are "athletes with single through knee or above knee limb deficiency competing with a prosthesis", and Class T64, where competitors are "athletes with unilateral below knee limb deficiency competing with a prosthesis" [33]. It is suggested that increased inter-limb asymmetry exists in lower limb amputees, with asymmetry being related to the proximity level of the amputation [34][35][36]. Nevertheless, past research has examined the biomechanical parameters of elite-level long jumpers with transtibial and transfemoral amputation [37][38][39][40][41][42][43][44][45], as well as with upper arm amputation [46].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to unilateral lower limb amputees, two classes are acknowledged by World Para-Athletics and by the International Paralympic Committee (IPC) [33]: Class T63, where competitors are "athletes with single through knee or above knee limb deficiency competing with a prosthesis", and Class T64, where competitors are "athletes with unilateral below knee limb deficiency competing with a prosthesis" [33]. It is suggested that increased inter-limb asymmetry exists in lower limb amputees, with asymmetry being related to the proximity level of the amputation [34][35][36]. Nevertheless, past research has examined the biomechanical parameters of elite-level long jumpers with transtibial and transfemoral amputation [37][38][39][40][41][42][43][44][45], as well as with upper arm amputation [46].…”
Section: Introductionmentioning
confidence: 99%
“…However, the non-optimised gait pattern from these prostheses can stress the healthy limbs and joints, causing injury after prolonged use. A classical example is the SACH foot, which has an energy efficiency estimated up to 31% [9]. Users are required to manually control these solid prosthetics, and this is typically described as passive control.…”
mentioning
confidence: 99%
“…The springs themselves can either be mechanical spring structures made of metal, plastic or composite materials, or pneumatic springs relying on air or fluidic pressure as the restoring force. Seattle and Flex come in various design embodiments, with energy efficiency estimated up to 52% and 84%, respectively [9].…”
mentioning
confidence: 99%
“…Originally, energy storing feet were designed for sports, but research led to adaptations suited for normal walking [180]. The earliest of these designs, termed Dynamic Elastic Response feet, borrowed the flexible keel and merged them with the cushioned heel of Solid-Ankle Cushioned-Heel (SACH) feet, see Figure 2.20 [181].…”
Section: Prosthetic Foot Design 221 Early Passive Prostheticsmentioning
confidence: 99%